Analisis Perbandingan Pengalaman Konsumen Terhadap Strategi Bisnis Dalam E-Commerce: Studi Kasus Shopee, Lazada, Dan Tokopedia - Ujung, Adelia Marwa; Adisa, Yunda; Nurbaiti (Journal Of Informatics And Busisnes, 2023)
The purpose of this research is to compare customer experiences in e-commerce. Electronic commerce is a global phenomenon that has changed the way businesses interact with consumers. It involves buying, selling and exchanging goods and services through online platforms. E-commerce has grown rapidly along with advances in information technology in business strategies. However, the challenges faced in e-commerce include the security of online transactions, intense competition, and the need to build customer trust. Examples of e- commerce are SHOPEE, LAZADA, TOKOPEDIA and others. It's just that in this research the researcher will compare the 3 studies in terms of customer experience. SHOPEE, LAZADA AND TOKOPEDIA are three e-commerce platforms operating in Southeast Asia, including Indonesia. By using quantitative methods.